2011
DOI: 10.1007/978-1-61779-433-9_18
|View full text |Cite
|
Sign up to set email alerts
|

Yeasts as a Tool for Heterologous Gene Expression

Abstract: The yeasts Saccharomyces cerevisiae and Pichia pastoris are attractive hosts for production of human proteins. The main advantages offered by these systems are the well-developed and easily accessible genetic tools, rapid growth, the simple and inexpensive culture media, and many of the cellular and metabolic processes found in higher eukaryotes are conserved in both yeast species. In this chapter, we describe the production of two proteins of therapeutic interest: the human P53 tumor suppressor and the viral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 23 publications
0
19
0
Order By: Relevance
“…After Bax, human p53 was the second heterologous proapoptotic gene that, although not present in the yeast genome, found to induce apoptosis‐like cell death when expressed in S. cerevisiae , thereby reinforcing the hypothesis that the apoptotic processes are conserved throughout the evolution from yeast to mammalian cells (Ligr et al ., ; Hadj Amor et al ., ; Greenwood & Ludovico, ). p53 induces yeast cell death with characteristic markers of apoptosis, such as DNA strand cleavage, the externalization of phosphatidylserines, and accumulation of ROS (Hadj Amor et al ., ; Mokdad‐Gargouri et al ., ). Very recently, it was reported that cell death induced by p53 expression in yeast is rather Yca1p independent and mainly mediated by Nuc1p (Palermo et al ., ), suggesting the importance of mitochondria in the p53‐induced cell death in yeast.…”
Section: P53mentioning
confidence: 97%
“…After Bax, human p53 was the second heterologous proapoptotic gene that, although not present in the yeast genome, found to induce apoptosis‐like cell death when expressed in S. cerevisiae , thereby reinforcing the hypothesis that the apoptotic processes are conserved throughout the evolution from yeast to mammalian cells (Ligr et al ., ; Hadj Amor et al ., ; Greenwood & Ludovico, ). p53 induces yeast cell death with characteristic markers of apoptosis, such as DNA strand cleavage, the externalization of phosphatidylserines, and accumulation of ROS (Hadj Amor et al ., ; Mokdad‐Gargouri et al ., ). Very recently, it was reported that cell death induced by p53 expression in yeast is rather Yca1p independent and mainly mediated by Nuc1p (Palermo et al ., ), suggesting the importance of mitochondria in the p53‐induced cell death in yeast.…”
Section: P53mentioning
confidence: 97%
“…Chemical inducers, such as IPTG, methanol or galactose, have been profusely employed for inducible gene regulation despite their obvious limitations including potential interference with metabolic processes, difficult removal from the culture media once added, and insufficient temporal and spatial/dose resolution (1). In addition, the cost of chemical inducers can restrict their uses in some industrial applications, whereas temperature induction or constitutive gene expression are chosen based on cost efficiency regardless of their far-from-optimal characteristics (2). Light constitutes a promissory alternative for the control of gene expression, considering its low cost, reduced toxic effects, adjustable levels, and high temporal and spatial resolution (3).…”
Section: Introductionmentioning
confidence: 99%
“…S. cerevisiae SIC, generated using the pSynInsCPOT plasmid for increased insulin production when compared with the conventional strain, is a representative example [26,27]. Beyond S. cerevisiae, P. pastoris has been used to produce the human p53 tumor suppressor protein [28], and Schizosaccharomyces pombe has been widely used to produce hepatitis vaccines [24].…”
Section: Wine Beer and Breadmentioning
confidence: 99%